Different Approaches to Managing Innovation Activities: An Analysis of Strong, Moderate, and Modest Innovators - Prokop, Viktor; Stejskal, Jan (My University, 2017)
The European Commission annually publishes its Innovation Union Scoreboard, which provides a comparative assessment of the EU member states’ research and innovation performance. The countries are divided into four groups according to their innovation performance: innovation leaders, strong innovators, moderate innovators, and modest innovators. In this paper, we have selected countries whose innovation performance was close to, below, or well below that of the EU average in 2015, and we have performed microeconomic analysis of the situation in these countries’ firms to analyse the conditions of their innovation environment and uncover barriers to their innovation activities. We analysed firms in the manufacturing industries in Slovenia (a strong innovator), Croatia (a moderate innovator), and Romania (a modest innovator) by using original multiple regression models and data from the 2010–2012 Community Innovation Survey. The results demonstrate the different backgrounds for innovation in each country. In Romania, there is a lack of both a satisfactory environment for innovation and sufficient capacity for absorbing public funds; investment into innovation-related activities is also absent. In Croatia, the innovation potential has not been fully exploited. However, we show that the appropriate targeting of innovation determinants (e.g., collaboration with different partners or public financing) could lead to the creation of synergies and spillover effects that would be able to support their innovative activities and strengthen the country’s competitiveness. There is a completely different situation in Slovenia. Firms there effectively utilize the various determinants of innovation activities, and these determinants have strong influence when utilized on their own. On the other hand, results also show that certain significant combinations of determinants of innovation activities are missing in Slovenia.
Rozdílné přístupy k řízení inovačních aktivit: analýza silný, pokročilých a mírně pokročilých inovátorů
Keywords: Innovation; Entrepreneurs; Innovation Management; Strong; Moderate; Modest Innovators; inovace; podnikatel; inovační management; silný, pokročilý a mírně pokročilý inovátor